(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In the world all in countries like, the population in Uzbekistan is between tuberculosis with of illness increase, disease fast developing, widespread, severe types, as well as of patients to drugs resistant from mycobacteria illnesses record is being done and is increasing. In our republic tuberculosis of the disease to spread inconvenient ecological situation, population socio-economic situation, population between migration , this including HIV infection and AIDS patients number increase reason However, the last in years intense and wide in scope preventive and to the epidemic against of events and the DOTS strategy implementation to be done as a result illness, death indicators one until to stabilize and to decrease achieved.